Assessing the economic impacts of marine protected area in Quilitisan, Calatagan, Batangas: An input to coastal resource management - Lunar, Bernardo C. (Animo Repository, 2014)
One of the management goals of the Verde Island Passage Marine Corridor is to increase the area and numbers of well managed Marine Protected Areas by the year 2018. The establishment and maintenance of these MPAs are faced with issues on sustainability. The question on whether they create economic sense is answered by looking into the generation of benefits that are at least equal to the costs they incur. Employing the descriptive method of study, it assessed the mangrove related ecotourism impacts inside the MPA of Quilitisan, Calatagan Batangas. Secondary data came from the management of the Calatagan Mangrove Forest Conservation Park (CMFCP). The study revealed that compared to the estimated number of visitors in the nearby resorts, the park is still behind on the number of its visitors. Relying heavily on its revenue from entrance fees, services rentals and donations, its operation is not that sustainable as it lacks a fund for maintenance and site development. With the survey and FGDs conducted, it was deduced that the ecotourism experience being offered by the CMFCP is satisfying to the visitors as reflected on their mean value of their WTP amounting to Php 150.00 which is higher than the current payment scheme. The value is commensurate with the raise that the management plans to implement.